A Vicinal Electrophilic Diborylation Reaction Furnishes Doubly Boron‐Doped Polycyclic Aromatic Hydrocarbons. Issue 20 (12th April 2017) - John, Alexandra; Bolte, Michael; Lerner, Hans‐Wolfram; Wagner, Matthias
Abstract: Ten examples of unsymmetrically benzannulated, boron‐doped polycyclic aromatic hydrocarbons (B‐PAHs) were prepared by a one‐pot protocol using 4, 5‐dichloro‐1, 2‐bis(trimethylsilyl)benzene (1 ), BBr3, and selected PAHs—among them anthracene, benzo[ a ]pyrene, biphenylene, and fluoranthene. After mesitylation at the boron centers, the resulting air‐ and water‐stable products were investigated by 1 H/ 11 B{ 1 H}/ 13 C{ 1 H} NMR spectroscopy, X‐ray crystallography, cyclic voltammetry, and UV/Vis absorption/emission spectroscopy. The experiments were augmented by DFT calculations. Most of the B‐PAHs are brightly luminescent ( Φ PL up to 90 %) and undergo reversible reduction at moderate half‐wave potentials. The two chloro substituents of1 are not only mandatory for accomplishing efficient diborylation, but can subsequently be used for Stille‐type coupling reactions to introduce 2‐thienyl moieties. Alternatively, Cl/H exchange is achievable with HSiEt3 in a quantitative, Pd‐catalyzed transformation. Abstract : Vicinally boron‐doped polycyclic aromatic hydrocarbons (B‐PAHs) were prepared in a three‐component reaction between a PAH, BBr3, and an electron‐poor 1, 2‐bis(trimethylsilyl)benzene. This approach provides a screening tool for libraries of B‐PAHs.